STUDI PROVENANCE BATUPASIR FORMASI WALANAE DAERAH LALEBATA KECAMATAN LAMURU KABUPATEN BONE PROVINSI SULAWESI SELATAN - Muhammad Ardiansyah; Mutia Farida; Ulva Ria Irvan (Jurnal Penelitian Geosains, 2015)
Almost of Walanae Formation consist of siliciclastic rocks. Provenance study is needed to determinate the source rocks because these rocks formed from earlier rocks. Administratively, the study area is located in Lalebata area, Lamuru District, Bone Regency, South Sulawesi Province.The purpose of this research is to study the provenance of Walanae Formation sandstone. The method were used measuring section and petrography analysis that used in genetic and empiric classification. Based on thin section analysis by compare between the monoquarst and polyquarst. The sandstone provenance of the area are plutonic igneous rocks, volcanic rocks and metamorphic rocks. The result of this study indicate that provenance of the Walanae sandstone derived from arround Formations are Igneous rocks and metamorphic rocks and included as Recycled Orogen and Mamatic Arc Provenance type.Keywords: Walanae Formation, Provenance, monoquarst, polyquarst, Recycled Orogen, Magmatic Arc Provenance